FINANCIAL SYSTEM SINERGY : FINANCIAL INCLUSION, FINTECH, AND CBDC - Loureine Patricia Sumual; Ivonne Stanley Saerang; Sri Murni; Joy Elly Tulung (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The interconnection between fintech, financial inclusion, and central bank digital currency (CBDC) presents a transformative opportunity to overcome the challenges of financial access and foster a more inclusive financial ecosystem. Fintech innovations plays an important role in facilitating the development, adoption, and usability of CDBC, effectively enhancing its accessibility and user-friendliness, particularly fo rundeserved populations. By leveraging fintech solutions, CBDC can significantly advance financial inclusion by providing individuals and businesses with convenient, affordable, and secure digital financial services. This integration necessistates collaborative efforts among fintech companies, central banks, and regulatory bodies to ensure a successful implementation. Through this collaboration, a more inclusive and efficient financial system can be established, benefitting individuals, businesses, and society as a whole.